2010
DOI: 10.1002/lary.21120
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of intraoral removal over submandibular gland resection for proximal submandibular stones

Abstract: Intraoral removal of proximal submandibular stones has several advantages over SMG resection. Based on our results, we suggest that our intraoral removal method be selected as the primary procedure for the removal of proximal submandibular stones rather than SMG resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…Nonetheless, extended incision of the duct has been constantly preferred as a gland preserving management. [8] A prospective randomized study by Eun, et al (2010) to compare the intra-oral and trans-cervical removal of proximal located submandibular sialolith found that the intra-oral technique have a slight advantage over the later, though the sialoliths in this study were smaller in size with mean size of 5.2 mm for the intra-oral approach and 9 mm for the trans-cervical approach. [24] Worldwide, significant numbers of patients with giant sialoliths are treated by resection of the submandibular gland.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nonetheless, extended incision of the duct has been constantly preferred as a gland preserving management. [8] A prospective randomized study by Eun, et al (2010) to compare the intra-oral and trans-cervical removal of proximal located submandibular sialolith found that the intra-oral technique have a slight advantage over the later, though the sialoliths in this study were smaller in size with mean size of 5.2 mm for the intra-oral approach and 9 mm for the trans-cervical approach. [24] Worldwide, significant numbers of patients with giant sialoliths are treated by resection of the submandibular gland.…”
Section: Discussionmentioning
confidence: 78%
“…[8] A prospective randomized study by Eun, et al (2010) to compare the intra-oral and trans-cervical removal of proximal located submandibular sialolith found that the intra-oral technique have a slight advantage over the later, though the sialoliths in this study were smaller in size with mean size of 5.2 mm for the intra-oral approach and 9 mm for the trans-cervical approach. [24] Worldwide, significant numbers of patients with giant sialoliths are treated by resection of the submandibular gland. [2] Conventionally, if the gland has been damaged by recurrent infection, obstruction and fibrosis or calculi have developed within the gland, and the structural damage acquired predisposes the gland to chronic disease and frequent impairment of the gland may necessitate removal.…”
Section: Discussionmentioning
confidence: 94%
“…This may lead to complications such as postoperative scarring and the possibility of the mandibular branch damage of the facial nerve. In consideration of the study shown that the function of salivary glands can be fully restored by simply removing the sialolith, it would be necessary to consider the removal of sialolith by an intraoral approach first if possible [13,14]. Recently, non-invasive treatments have been introduced, and an intraoral approach using sialendoscopy has been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Recently minimal invasive methods were defined such as extracorporeal lithotripsy, interventional radiology and operative sialoendoscopy (12,13). Although these new techniques provide severe benefit to the diagnosis of large salivary gland stones, they may still remain insufficient especially for the treatment of large stones (14). Since almost half of the submandibular gland stones are localized at the distal 1/3 rd part of the duct, they can be easily removed surgically with an incision performed to mouth floor.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need of hesitation for salivary fistulas may develop on incision. If the surgeon performing this application wishes, can marsupialise the suture edges to mouth floor mucosa (14). Iqbal et al (17) have reported that after removal of stone in Wharton duct, they intraorally marsupialise the opening in the duct and create a 2 cm sized opening.…”
Section: Discussionmentioning
confidence: 99%